(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This paper presents the development and experimental validation of a novel two-degree-of-freedom pendulum energy harvester (2DoPe), designed to convert wave-induced motion into electrical energy. The primary objective is to briefly present the mathematical modeling of the 2DoPe system, outline the process of designing of the prototype, describe the testing facility used for validation, and provide preliminary experimental results. The 2DoPe employs a unique mechanical design featuring two rotational degrees of freedom, allowing it to capture energy from multidirectional waves. The mathematical modeling of the system was conducted using both SimScape and an analytical approach. This allowed for the simulation of the harvester’s nonlinear dynamics, capturing bifurcations and chaotic behavior, and optimizing the system for efficient energy conversion under varying wave conditions. Following the numerical modeling phase, a scaled prototype of the 2DoPe was constructed. The prototype features variable mass and inertia components, which can be adjusted to optimize the system’s energy harvesting capability. The system includes a comprehensive data acquisition system, which records key parameters such as angular displacement, velocity, and force, as well as the performance of the power take-off (PTO) units, which convert mechanical motion into electrical power. The prototype was then tested on a Stewart platform, a high-performance six-degree-of-freedom motion simulator, which replicates wave-induced motions and provides a precise and controlled environment for testing. The integration of hardware-in-the-loop (HIL) with numerical models allows for real-time testing of the system while maintaining full control over experimental variables. Preliminary results from the tests confirmed the harvester’s ability to adapt to varying wave motions, providing stable and efficient energy output. The prototype showed sensitivity to key design parameters, such as the variable pendulum mass, inertia, and arm length, allowing for systematic testing and optimization. These results validate the numerical models and demonstrate the scalability of the 2DoPe system for different applications, ranging from small oceanographic instruments to larger offshore devices. The 2DoPe harvester’s innovative design, compactness, and adaptability to variable sea states make it particularly suitable for integration into autonomous measurement systems, offering a reliable, low-maintenance energy solution for remote oceanographic applications. This paper lays the groundwork for further optimization of the prototype, integration of advanced control strategies, and testing in more realistic environments, contributing to the advancement of renewable wave energy technology.